Reincarnating the Identity Theory - Myin, Erik; Zahnoun, Farid (Frontiers in Psychology, 2018)
The mind/brain identity theory is often thought to be of historical interest only, as it has allegedly been swept away by functionalism. In this paper we reconsider the merits of an updated form of identity theory, that is one in which the identities concern not experiences and brain phenomena, but experiences and organism-environment interactions. Such an embodied identity theory, so we will claim, retains the main ontological insight of its parent theory, by implying there is no genuine problem about having to show how the mental derives from the physical. At the same time, by invoking organism-environment interactions, the explanatory resources of the identity approach are considerably added to. We argue that the classical multiple realization argument against identity theory is built on not recognizing that the main claim of the identity theory concerns the relation between experience and descriptions of experience, instead of being about relations between different descriptions of experience. We emphasize that the embodied identity theory we propose is not ontologically reductive, and does not disregard experience.